The Global South and US trade policy: Structural exposure and economic vulnerability in selected African countries - Frederik Stender; Tim Vogel; Lukas Kornher; Zoryana Olekseyuk; Sascha Berndt; Andreas Edele (German Institute of Development and Sustainability (IDOS), 2025)
United States (US) trade policy has undergone a series of significant changes introducing far-reaching uncertainty for trading partners in both the short and long term. Among the most vulnerable to these changes are low- and middle-income countries. Anticipating the potential impact of proposed or enacted US trade measures ex-ante is difficult. Therefore, this discussion paper examines the structural vulnerabilities of a selection of African countries - Lesotho, Madagascar, Côte d'Ivoire, South Africa, and Tunisia - to recent shifts. Using descriptive trade data, the paper maps direct and indirect channels of exposure and highlights the structural constraints that amplify vulnerability. While Africa is not among the most directly exposed regions, several countries face significant risks due to concentrated export structures, reliance on a few trade partners, and limited capacity to redirect trade in the short term. This highlights the strategic importance for African countries to strengthen regional integration, industrial upgrading, and reduce external dependencies.
Keywords: 320; US trade policy; trade policy uncertainty; Africa; tariff vulnerability; structural trade exposure